Pengaruh Pemberian Pakan Cacing Sutra (Tubifex sp.) Yang Berbeda Terhadap Pertumbuhan Dan Kelangsungan Hidup Benih Ikan Nilem (Osteochilus hasselti) - Afrizal Candra Aditya; Eric Armando; Annisa Novita Sari (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2023)
ABSTRACNilem fish (Osteochilus hasselti) is a freshwater fish native to Indonesia which is greatly appreciated by the public by its eggs and larvae, the morphology of nilem fish has a flat body form, the mouth can be ripped off. The purpose of this study was to determine the best phase of the silk worm (Tubifex sp.) in the growth rate and survival of nilem fish seeds (Osteochilus hasselti). This research took place from November to December 2021. The research was located in Petuguran Village, Punggelan District, Banjarnegara Regency, Central Java. The search method used was a completely randomized design with 3 treatments and 3 repeats. Treatments in this study were A (baby silk worms), B (juvenile silk worms) and C (adult silk worms). Data were analyzed using Analysis of Variance (ANOVA), followed by a further Ducan’s Multiple Range Test. Parameters observed in the study included absolute weight growth, absolute length growth, feed conversion ratio, and survival. The results of these observations had a significant effect on the increase in absolute weight with the highest treatment found in treatment C (adult silk worms) of 1.56 grams and the increase in absolute length had a significant effect with the highest treatment found in treatment C (adult silkworms) of 8.47 centimetres. However, it does not have a significant effect on the feed conversion ratio and the survival of nilem fish seeds (Osteochilus hasselti). Keywords: silkworms (Tubifex sp.), FCR, nilem fish, survival rate, fish growth